Analisis Dampak Modernisasi Terhadap Perilaku Siswa Sekolah Dasar Pada Aspek Sosial Budaya - Febby Nur Adhari; Gina Amalia; Tin Rustini (Pusat Riset dan Inovasi Nasional, 2024)
Modernization isa process of changing societies and cultures with all its aspects from traditional to modern. Modernization, while having a positive effect, can also have a negative impact that one of them is having on the behavior of elementary school students. These effects can happen if we cannot strain that modernization. Therefore as teachers we should be able to minimize the emergence of harmful negative effects on the creation of student character. The results of this study suggest that modernization has hada significant impact on the behavior of elementary school students. This is demonstrated by such oft viewed negative behaviors as brawling, social strife, social promiscuity, misuse of the Internet and cell phones that cause students to become irritable and socially impaired. The research method used was the literacy study of several accredited journals according to the research discussion. This study is intended to enable readers to know the impact that modernization of students' behavior in elementary schools and teachers can minimize the negative effects that will happen in students.